EFEKTIVITAS DAN UPAYA MAKSIMALISASI PENGELOLAAN ZAKAT PRODUKTIF OLEH BAZNAS KABUPATEN PINRANG TERHADAP PENINGKATAN KESEJAHTERAAN MUSTAHIK - Amira Husnul Khatimah; Nurfadil Arham (Department of Management Zakat and Waqf, 2025)
Analysis of the effectiveness of productive zakat management on the empowerment of mustahik in Pinrang Regency (case study of BAZNAS Pinrang Regency). The objectives of this study are to determine: (1) The form of productive zakat management at BAZNAS Pinrang Regency. (2) The effectiveness of methods or strategies of productive zakat management on the empowerment of mustahik at BAZNAS Pinrang Regency. This study used a qualitative research method with field research and data collection methods consisting of observation, interviews, and documentation. The results of this study show that: (1) The form of productive zakat management at BAZNAS Pinrang Regency is carried out through the Pinrang Peduli program, which is divided into traditional productive and creative productive programs and is specifically aimed at mustahik who will build businesses or develop existing businesses. (2) The effectiveness of the methods or strategies in productive zakat management for the empowerment of mustahik at BAZNAS Pinrang Regency is considered quite effective, as seen from how BAZNAS created the methods, namely, first, through planning. This planning is categorized by means of organization, implementation, mobilization, and supervision. Second, data collection or selection of mustahik needs to be carried out in empowering mustahik. This is because it is considered to provide effectiveness in the management of zakat so that assistance is not misdirected.